2012
DOI: 10.1073/pnas.1114243109
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts of US reactive nitrogen

Abstract: Fossil fuel combustion and fertilizer application in the United States have substantially altered the nitrogen cycle, with serious effects on climate change. The climate effects can be short-lived, by impacting the chemistry of the atmosphere, or long-lived, by altering ecosystem greenhouse gas fluxes. Here we develop a coherent framework for assessing the climate change impacts of US reactive nitrogen emissions, including oxides of nitrogen, ammonia, and nitrous oxide (N 2 O). We use the global temperature po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(115 citation statements)
references
References 47 publications
1
114
0
Order By: Relevance
“…Current estimates are that human creation of reactive nitrogen (both oxidized and reduced nitrogen) increased by over an order of magnitude from ∼ 15 Tg N yr −1 to ∼ 187 Tg N yr −1 between 1860 and 2005 (Galloway et al, 2008). This increase is one of the primary causes of air pollution, contributing directly to the production of urban ozone and secondary organic aerosol (e.g., Carlton et al, 2010;Pye et al, 2010;Pinder et al, 2012;Rollins et al, 2012). The increase in NO x also results in an increase in the global background of OH (e.g., Wild et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Current estimates are that human creation of reactive nitrogen (both oxidized and reduced nitrogen) increased by over an order of magnitude from ∼ 15 Tg N yr −1 to ∼ 187 Tg N yr −1 between 1860 and 2005 (Galloway et al, 2008). This increase is one of the primary causes of air pollution, contributing directly to the production of urban ozone and secondary organic aerosol (e.g., Carlton et al, 2010;Pye et al, 2010;Pinder et al, 2012;Rollins et al, 2012). The increase in NO x also results in an increase in the global background of OH (e.g., Wild et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric nitrogen (N) deposition has already increased by three-to five-fold over the past century due to fossil fuel combustion, fertilizer production, and cultivation [1]. N deposition is predicted to increase in many parts of the world in the next decades because of the rapid development and expansion of industrial and agricultural activities and thus has been considered a major scientific challenge [2].…”
Section: Introductionmentioning
confidence: 99%
“…Intensive arable agriculture is inherently leaky in terms of nutrient cycling (Pinder et al 2012), and is often the dominant land use on fertile lowland plains where it is responsible for large eutrophication loadings to surface waters. Hitherto, consequential LCA studies of bioenergy systems have emphasised uncertain ILUC effects attributable to food production displacement, which Berndes et al (2013) argue has distracted policy makers from genuine long-term GHG mitigation that can be achieved by bioenergy deployment.…”
Section: Resultsmentioning
confidence: 99%
“…Projected increases in demand for agricultural commodities suggest a need to ''spare'' non-farmed high-nature value areas from agricultural expansion via ''sustainable intensification'' (Garnett et al 2013). Although current intensive crop and livestock systems may produce food with a lower GHG intensity than extensive systems when global land use change (LUC) is considered (Burney et al 2010;Havlík et al 2014), such systems diminish the delivery of other ecosystem services (Haas et al 2000;Firbank et al 2013), especially via large releases of reactive nitrogen to air and water (Dalgaard et al 2012;Pinder et al 2012) that can be particularly problematic in the vicinity of large, enclosed water bodies. Kiedrzyńska et al (2014) found strong Electronic supplementary material The online version of this article (doi:10.1007/s13280-016-0790-9) contains supplementary material, which is available to authorized users.…”
Section: Bioenergy and Food Productionmentioning
confidence: 99%